2020
DOI: 10.1016/j.transci.2020.102820
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a centenarian with coronavirus disease 2019 (COVID-19) using convalescent plasma

Abstract: Background: Because treatment options for coronavirus disease 2019 (COVID-19) are very limited, the use of convalescent plasma has bee explored. Case presentation and treatment: A male centenarian with cough and dyspnea for 2 months was diagnosed with COVID-19. Without effective treatments and with the increased risks of antiviral therapy for the elderly, this patient was given convalescent plasma. The viral load, complete blood count, inflammatory indicators, vital signs, and clinical symptoms were observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…Data on the outcomes of these trials have been limited and to date, preliminary results from only a few small cohorts and one randomized clinical trial have been published. Results from a randomized clinical trial did not show a benefit 6,7 , while results from the small cohorts suggested clinical benefit but lacked controls for proper interpretation [8][9][10][11] . Although preclinical research indicated a limited protective effect of hamster serum when given to hamsters infected with SARS-CoV-2 early in the disease course 12,13 , effects of human plasma have not been analyzed in this animal model.…”
Section: Introductionmentioning
confidence: 93%
“…Data on the outcomes of these trials have been limited and to date, preliminary results from only a few small cohorts and one randomized clinical trial have been published. Results from a randomized clinical trial did not show a benefit 6,7 , while results from the small cohorts suggested clinical benefit but lacked controls for proper interpretation [8][9][10][11] . Although preclinical research indicated a limited protective effect of hamster serum when given to hamsters infected with SARS-CoV-2 early in the disease course 12,13 , effects of human plasma have not been analyzed in this animal model.…”
Section: Introductionmentioning
confidence: 93%
“…Subsequently, the patient was given convalescent plasma. Although still being heavily researched, it has worked effectively in hospitals, notably successfully treating a centenarian with COVID-19 [7]. Other medicinal therapies have been successfully paired and repurposed to treat COVID-19 pneumonia, such as chloroquine and clarithromycin [8].…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvement of laboratory indicators and clinical symptoms was observed. SARS-CoV-2 viral load decreased after the first transfusion (from 2.55 × 10 4 to 1.39 × 10 3 copies RNA/ml) and became undetectable (13 days of hospitalization) after the second one [94]. Another study reported treatment of 10 patients, with confirmed by RT-PCR infection, treated with CP transfusion (ChiCTR2000030046) [46].…”
Section: Convalescent Plasma Therapymentioning
confidence: 99%
“…A negative result of RT-PCR testing for SARS-CoV-2 is also clearly expected [135]. CP should also contain sufficient amount of SARS-CoV-2 -specific antibodies [94]. Recommendations of FDA for investigational CP treatment are also available at FDA site (https://www.fda.gov/vaccines-blood-biologics/ investigational-new-drug-ind-or-device-exemptionide-process-cber/recommendations-investigationalcovid-19-convalescent-plasma).…”
Section: Convalescent Plasma Therapymentioning
confidence: 99%